Analisis Break Event Point (BEP) dan Harga Pokok Produksi (HPP) Produk Frozen Food di Kecamatan Ambarawa Kabupaten Pringsewu (Studi Kasus pada CV Lezatku Food) - Kifah Soleha; Dyah Aring Hepiana Lestari; Yuliana Saleh (Journal of Food System & Agribusiness, 2022)
This study aims to analyze the amount of the break-even point of revenue, production, and price as well as to analyze the cost of production issued by the frozen food agroindustry as a consideration in determining the selling price for marketed products. The research method used is a case study method at CV Lezatku Food which is located in Ambarawa Sub-district, Pringsewu Regency. Determination of the location is done purposively with the consideration that the agroindustry is an active agroindustry producing five variants of frozen food with meat and fish as raw materials. Respondents in this study were owners and supervisors of CV Lezatku Food. Data collection is carried out from November 2021 to December 2021. Data analysis is carried out using break event point (BEP) analysis and cost of goods manufactured using the full costing method. The results showed that the acceptance, production, and price of each frozen food product variant at CV Lezatku Food were already greater than the break event point calculation results, meaning that production activities in the frozen food agroindustry were feasible to continue. The result of calculating the cost of production for each frozen food product variant is smaller than the prevailing selling price. This shows that the selling price determined by the agro-industry is good, with an average profit margin of 53,12 percent.